HIV transmission from drug injectors to partners who do not inject, and beyond: modelling the potential for a generalized heterosexual epidemic in St. Petersburg, Russia. - Mills, Harriet L; White, Edward; Colijn, Caroline; Vickerman, Peter; Heimer, Robert (Drug and alcohol dependence, 2013)
HIV infection is prevalent among drug injectors in St. Petersburg and their non-injecting heterosexual partners (PIDUs). There are fears that sexual transmission of HIV from IDUs to PIDUs may portend a self-sustaining, heterosexual epidemic in Russia.
Keywords: Epidemics; Female; Heterosexuality; HIV Infections; Humans; Male; Models, Psychological; Prevalence; Russia; Sexual Partners; Substance Abuse, Intravenous; Unsafe Sex